PERANCANGAN ULANG TATA LETAK FASILITAS MENGGUNAKAN METODE ARC DI TARZAN PHOTO - ALBERT, ALBY; YULIANTO, DARMAWAN; SETIAWAN, DEDI; WIJAYANTO, ERWIN (Universitas Dirgantara Marsekal Suryadarma, 2023)
Tarzan photo is a photography company operating in the photo studio on Jl.KH. Hasyim Ashari, Gambir Jakarta, the center of the problem with this photo company is the route that consumers take and less efficient service which causes chaos on the route and this photo company has not been able to meet demand optimally. the layout is still not quite right, where to transfer materialsbetween departments, the distance required is quite far so it takes quite a long time. Apart from that, this causes the flow of service to become irregular and the relationship between departmentsto be less effective, such as the location of the traffic room being too far from the sales room. Giventhese existing problems, research was carried out using the Activity Relation Chart (ARC) methodwith the hope of minimizing the length of the material and consumer paths, indirectly shortening the traffic distance in handling photo services and gaining customer satisfaction. The results of the layout design obtained that the distance length in the initial conditions was 166 m, while the length of the track distance in the proposed conditions was 119 m. This means that when designing the proposed layout conditions using the Activity Relation Chart (ARC) method, the length of the track distance can be minimized by 47 m, from the initial conditions.